Ball-milled FeP/graphite as a low-cost anode material for the sodium-ion battery. Issue 98 (23rd October 2015) - Yang, Qiu-Ran; Li, Wei-Jie; Chou, Shu-Lei; Wang, Jia-Zhao; Liu, Hua-Kun
<x xml:space="preserve">Abstract</x> Our results suggest that by using a low-energy ball-milling method, a promising FeP/graphite anode material can be synthesized for the sodium battery.